Macrolactonization of methyl 15-hydroxypentadecanoate to cyclopentadecanolide using KF-La/γ-Al2O3 catalyst. Issue 9 (7th September 2022) - Cheng, Haijun; Yu, Chang; Wang, Hongyun; Liu, Xiongmin; Ma, Li; Lai, Fang
Abstract : It has been a challenge to synthesize macrolide musk in excellent yields with high purity. KF-La/γ-Al2 O3 catalyst was prepared from a highly basic mesoporous framework using a mild method. The prepared KF-La/γ-Al2 O3 catalyst was employed for the synthesis of cyclopentadecanolide from methyl 15-hydroxypentadecanoate. The morphology and structure of prepared catalysts were characterized using XRD, TG-DTG, SEM, EDX, TEM, BET and CO2 -TPD. The results revealed that the K3 AlF6 and LaOF are produced on the surface of KF-La/γ-Al2 O3, and LaO can promote the dispersion of KF on the surface of Al2 O3 . Catalysts pore size main distribution ranges between 10 and 30 nm, the maximum CO2 desorption temperature is 715°C when the La loading is 25%. Because F − ion has a higher electronegativity than O 2− ion, the KF-promoted metal oxide (Al2 O3 or/and La2 O3 ) contained more strong basic sites, compared with that of the corresponding metal oxide. The yield of cyclopentadecanolide obtained at 0.5 g KF-25La/γ-Al2 O3 catalyst and a reaction temperature of 190°C for 7 h were 58.50%, and the content after reactive distillation is 98.8%. The KF-La/γ-Al2 O3 catalyst has a larger pore size and basic strength, which is more conducive to the macrolactonization of long-chain hydroxy ester.